2023
DOI: 10.1186/s13148-023-01424-w
|View full text |Cite
|
Sign up to set email alerts
|

Long-term impact of paediatric critical illness on the difference between epigenetic and chronological age in relation to physical growth

Abstract: Background Altered DNA-methylation affects biological ageing in adults and developmental processes in children. DNA-methylation is altered by environmental factors, trauma and illnesses. We hypothesised that paediatric critical illness, and the nutritional management in the paediatric intensive care unit (PICU), affects DNA-methylation changes that underly the developmental processes of childhood ageing. Results We studied the impact of critical i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 39 publications
1
4
0
Order By: Relevance
“…Age dependency of vulnerability towards abnormal DNA methylation was somewhat greater, with a more pronounced hypomethylation of several CpG sites within HSD17B2 , HSD17B12 and CYP19A1 in children who at the time of PICU admission had already reached or passed the age of adrenarche as compared with younger children. This corresponds with our earlier finding of a higher vulnerability to epigenetic age deceleration of former PICU patients from the age of adrenarche onwards and into puberty [ 11 ].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Age dependency of vulnerability towards abnormal DNA methylation was somewhat greater, with a more pronounced hypomethylation of several CpG sites within HSD17B2 , HSD17B12 and CYP19A1 in children who at the time of PICU admission had already reached or passed the age of adrenarche as compared with younger children. This corresponds with our earlier finding of a higher vulnerability to epigenetic age deceleration of former PICU patients from the age of adrenarche onwards and into puberty [ 11 ].…”
Section: Discussionsupporting
confidence: 92%
“…For the differentially methylated positions in former PICU patients as compared with healthy children, we assessed whether there was an interaction with sex and/or age at exposure to critical illness and its treatments. We recently found that vulnerability to age deceleration of former PICU patients as compared with healthy children started from ± 6 years at exposure to critical illness and its treatments [ 11 ]. Therefore, we dichotomised age accordingly for the age-interaction analyses.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In previous studies in infants with congenital heart disease, impaired height trajectories were associated with worse neurodevelopmental outcomes [ 55 , 56 ]. However, head circumference at birth, postnatal factors, genetic comorbidity, and epigenetic changes are important factors which must be taken into account concerning impaired height trajectories and neuropsychological outcome [ 61 ]. Also, when evaluating outcome of children after PICU discharge, it is important to include baseline (health) status and family factors in multifactorial predictive models [ 62 , 63 ].…”
Section: Discussionmentioning
confidence: 99%